A Study on Uniaxial Compressive Strength and Ultrasonic Non-Destructive Analysis of Fine-Grained Soil in Seasonally Frozen Regions - Umar, Ibrahim Haruna; Fırat, Muge Elif (My University, 2022)
Understanding the physical and mechanical properties of soils subjected to freeze-thaw cycles, including both micro and macrostructures, is critical for achieving the required performance of structures employing it as a structural or support material. An experimental study was carried out on clay soil with varying water content (18%, 21.5%, and 23%) after repeated freeze-thaw cycles (0, 2, 5, 7, 12, and 15). The performance of soil was evaluated using unconfined compressive strength (UCS) and ultrasonic pulse velocity (UPV) tests. The experimental results demonstrated that UCS peak values were observed at the lowest water content before and after the freeze-thaw cycles. The stress-strain curves exhibited strain-softening behavior, and this condition transitioned to strain hardening behavior after freeze-thaw cycles with increment in the water content. Moreover, the highest values of UPV were observed to increase UCS values due to capillary forces at minimum water content. Also, an increase in the number of freeze-thaw cycles resulted in a decrease in the UPV. According to correlations between UPV and UCS values, the highest correlations for water contents were obtained at optimum water content, and a decreasing trend was observed after experiencing a number of freeze-thaw periods. In addition, the Grey Correlation Analysis was performed to show the degree of correlation between the UCS and UPV, water content as well as the freeze-thaw cycles. The results demonstrated that the UPV values have a greater impact on the UCS than other parameters.
Keywords: Clay soil; uniaxial compression test; ultrasonic pulse velocity test; seasonally frozen region